Characterization of metabolic profiles and lipopolysaccharide effects on porcine vascular wall mesenchymal stem cells. Issue 10 (1st March 2019) - Nesci, Salvatore; Bernardini, Chiara; Salaroli, Roberta; Zannoni, Augusta; Trombetti, Fabiana; Ventrella, Vittoria; Pagliarani, Alessandra; Forni, Monica
Abstract: The link between metabolic remodeling and stem cell fate is still unclear. To explore this topic, the metabolic profile of porcine vascular wall mesenchymal stem cells (pVW‐MSCs) was investigated. At the first and second cell passages, pVW‐MSCs exploit both glycolysis and cellular respiration to synthesize adenosine triphosphate (ATP), but in the subsequent (third to eighth) passages they do not show any mitochondrial ATP turnover. Interestingly, when the first passage pVW‐MSCs are exposed to 0.1 or 10 μg/ml lipopolysaccharides (LPSs) for 4 hr, even if ATP synthesis is prevented, the spare respiratory capacity is retained and the glycolytic capacity is unaffected. In contrast, the exposure of pVW‐MSCs at the fifth passage to 10 μg/ml LPS stimulates mitochondrial ATP synthesis. Flow cytometry rules out any reactive oxygen species (ROS) involvement in the LPS effects, thus suggesting that the pVW‐MSC metabolic pattern is modulated by culture conditions via ROS‐independent mechanisms. Abstract : Porcine vascular wall mesenchimal stem cells (pVW‐MSCs) exploit both glycolysis and cellular respiration to synthesize adenosine triphosphate (ATP). The metabolic profile depends on the cell passage and is susceptive to lipolysaccharide exposure. Culture conditions modulate pVW‐MSC bioenergetics via reactive oxygen species (ROS)‐independent mechanisms.